Kratom (Mitragyna speciosa) use and mental health: a systematic review and multilevel meta-analysis - Yang, Yuting; Müller, Christian P.; Singh, Darshan (European addiction research, 2024)
INTRODUCTION: Kratom (Mitragyna speciosa) is a medicinal tree native to Southeast Asia. The present multilevel meta-analysis describes the association between kratom use and the positive and negative indicators of mental health. - METHODS: A total of thirty-six articles were included in the meta-analysis to examine the associations, using a random-effects model. - RESULTS: The pooled effect size showed a very small positive association between kratom use and negative indicators of mental health {r = 0.092, 95% confidence interval (CI) = [0.020, 0.164], p < 0.05}, while no significant association was found with positive indicators of mental health (r = -0.031, 95% CI = [-0.149, 0.087], p > 0.05). Pooled effect sizes of specific mental health outcomes indicated that kratom use showed only a small positive correlation with externalizing disorders (r = 0.201, 95% CI = [0.107, 0.300], p < 0.001). No significant association was found between kratom use and quality of life (r = 0.069, 95% CI = [-0.104, 0.242], p > 0.05) and internalizing disorders (r = -0.001, 95% CI = [-0.115, 0.095], p > 0.05). Multilevel moderator analysis showed that the pooled effect size of the association between kratom use and substance use disorder was stronger in Malaysia (r = 0.347, 95% CI = [0.209, 0.516], p < 0.001), and with the mean age (β1 = -0.035, 95% CI = [-0.055, -0.014], p = 0.003), and the drug profile of those who were not co-using other drugs (r = 0.347, 95% CI = [0.209, 0.516], p < 0.001). - CONCLUSION: The meta-analysis supports the kratom instrumentalization concept, in that a positive gain from kratom consumption can be achieved without any significant adverse associations with mental health.